PSI-37 The effects of delaying initial colostrum feeding on gastrointestinal tract growth of neonatal bull dairy calves. (7th December 2018) - Pyo, J; Fischer, A; He, Z; Haines, D; Guan, L; Steele, M
Abstract: The objective of this study was to determine whether delaying the initial colostrum feeding has an effect on the growth of the neonatal calf gastrointestinal tract (GIT). Twenty-seven Holstein bull calves (42.55 ± 1.17 kg) were randomly allocated to one of the three colostrum feeding times (n = 9): 0, 6 and 12 h postnatally. Calves were fed pooled colostrum at 7.5% of BW, and commercial milk replacer at 2.5% of BW every 6 h thereafter. Calves were euthanized at 51 h of life and tissue from the proximal and distal jejunum was collected for histology analysis. Villi length and crypt depth were measured from brightfield histographs throughout the GIT and ultrastructure of ileum samples were analyzed using a transmission electron microscope. For statistical analysis a three-way ANOVA using proc MIXED model was used. Calves fed colostrum at 0 h had the shortest villi in the proximal jejunum compared to those fed colostrum at 6 and 12 h (337.6 ± 18.3 vs. 438.1 ± 18.3 vs. 377.4 ± 19.9 µm; 0 vs. 6 vs. 12 h, respectively; P = 0.001); villi in the distal jejunum were longer ( P = 0.002) for calves fed colostrum at 12 h by 103.8 ± 18.53 and 123.2 ± 14.71 µm compared to those fed colostrum at 0and 6 h, respectively. In contrast, crypt was deeper by 24.5 and 20.0 % ( P = 0.04) in the distal jejunum of calves fed colostrum at 0 h calves compared to those fed at 6 and 12 h, respectively. There were no differences in the GIT enterocyte ultrastructure among the treatments. However, all treatments showed extensive pinocytosis and vacuole formation in enterocytes. These results suggest that timing of colostrum feeding will differentially affect structural development in the small intestine, though maturation of the GIT occurs regardless of treatment.